Herbage accumulation and nutritive value of mixtures of deshograss and Vicia spp. in southern Ethiopia - Abera, M.; Tolera, Adugna; Nurfeta, A.; Geleti, D. (Wiley, 2022)
Grass and legume mixtures work well, but there are no data on the mixed planting of desho grass (Pennisetum glaucifolium) and Vicia species. A study was conducted to investigate whether forage dry matter yield (DMY) and quality can be improved by growing Vicia species in mixtures with desho grass. The experimental layout followed a randomized complete block design with four replications, where the treatments consisted of pure stands of three Vicia species Vicia dasycarpa, V. villosa, and V. sativa, desho grass and mixture of desho grass and each of the Vicia species. The results showed a positive effect of intercropping leading to greater herbage accumulation than expected from grass species sown in sole cropping. Growing Vicia species with desho grass resulted in higher yields and higher land equivalent ratio (LER), as well as increased crude protein (CP) content and digestibility compared to pure stand desho grass. Intercropping smooth vetch, hairy vetch, and common vetch gave 63, 67, and 48% more forage DMY than the pure stand desho grass, respectively. When desho grass was intercropped with Vicia species LER was greater by 9, 55, and 58% for common vetch, smooth vetch, and hairy vetch, respectively, over pure stand desho grass. Therefore, it can be concluded that growing a mixture of Vicia species with desho grass is a suitable practice to improve forage DM production and quality, and farmers can use land more efficiently by growing Vicia species with desho grass.